Identification of temperature anomalies in the western Caspian Sea in 2017 based on remote sensing data - A. A. Bagomaev; N. O. Guseynova (Юг России: экология, развитие, 2021)
Aim. The study of temperature anomalies in the western Caspian Sea based on space imagery materials in order to detect upwelling phenomena.Materials and Methods. We used temperature indicators of seawater for the summer season of 2017 when a sharp decrease by more than 2 °C in average daily temperature occurred. Space images were obtained from the specialized centres of Ocean Color NASA, Earth Science Data Systems NASA and SATIN. Remote sensing data were processed using SeaDAS and ArcGIS programs. Ground data were obtained from the resources of the Unified State System of Information about the Situation in the World Ocean (ESIMO). An ArcGIS database was created and maps compiled.Results. The first upwelling occurred on 9-17 June 2020. The minimum water temperature in the Makhachkala area was 14°C with an increase in salinity to 12%o over an area of 1,500 sq.km. An increase in the content of dissolved oxygen of up to 9.70 mg/l and pH 8.64 was recorded. A second upwelling of medium intensity occurred from 19 June-July 1 with a minimum temperature of 17.9C. The decrease in temperature was 2.8°C with an increase in salinity by 1%o. The surface area was 454 sq.km. A third case of upwelling was recorded from 26 August-September 1 and was characterised by a decrease in water temperature of 7.4C (near the coast, 17.1°C). The average salinity increase was 0.32%o while the 02 concentration was 8 mg/l over an area of 500 sq.km.Conclusion. Due to its large size, the Caspian Sea is characterised by spatial inhomogeneity of oceanological parameters, which can be recorded based on the results of processing satellite images and their verification using ground data. In the western part of the sea the upwelling is periodic and of different scales.